Stress distribution of secondary bending in single-lap bolted joints with dissimilar joining plates and plate types - Ahmad, Hilton (PENERBIT UTM PRESS, 2016)
Single-lap joints are an important class of bolted joint in the aerospace and civil engineering sectors. This type of joint is preferred as it can reduce weight and hence help to optimize fuel efficiency. However, bolted single-lap joints exhibit secondary bending due to eccentricity of the applied loads. Flexural of plates during tensile loading alters the contact regions in the single-lap joint significantly, resulting in more non-linear behaviour and a stress gradient across the plate thickness. 3-D bolted single-lap joint were modelled in ABAQUS CAE incorporating the effect of the bolt tension from application of a tightening torque. Current 3-D model used elastic properties based on smeared-out properties, the effect of joint construction is considered further by examining the stress in a composite-composite joint and comparing with a composite-steel joint. In a related investigation the effect of varying composite thickness in the composite-steel joints is also studied.